2016
DOI: 10.1002/asia.201600211
|View full text |Cite
|
Sign up to set email alerts
|

Facile Assembly of Benzo[b]naphtho[2,3‐d]azocin‐6(5 H)‐ones by a Palladium‐Catalyzed Double Carbometalation

Abstract: The palladium-catalyzed reaction of 2-alkynylanilines with 2-(2-bromobenzylidene)cyclobutanone as an efficient route to 7,8-dihydrobenzo[b]naphtho[2,3-d]azocin-6(5 H)-ones was developed. The fused eight-membered ring was constructed conveniently. During the reaction process, double carbometalation was involved, which resulted in excellent selectivity with the formation of three new bonds. This transformation is highly efficient and leads to fused polycycles in good to excellent yields with good functional grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Yao, Wu, and co-workers developed a novel facile and efficient route for the synthesis of benzo[ b ]naphtha[2,3- d ]azocinones 353 through a palladium-catalyzed reaction of 2-alkynylanilines 351 with 2-(2-bromobenzylidene)cyclobutanones 352 . 112 During the reaction process, double carbometalation resulting in the formation of three new bonds was involved (Scheme 105 ).…”
Section: Other Methodsmentioning
confidence: 99%
“…Yao, Wu, and co-workers developed a novel facile and efficient route for the synthesis of benzo[ b ]naphtha[2,3- d ]azocinones 353 through a palladium-catalyzed reaction of 2-alkynylanilines 351 with 2-(2-bromobenzylidene)cyclobutanones 352 . 112 During the reaction process, double carbometalation resulting in the formation of three new bonds was involved (Scheme 105 ).…”
Section: Other Methodsmentioning
confidence: 99%
“…Pd(II)‐catalyzed treatment of compound 8 with 2‐(2‐bromobenzylidene)cyclobutanone 203 led to the formation of benzo[ b ]naphtho[2,3‐ d ]azocin‐6(5 H )‐ones 207 (Scheme 63). This reaction passes from intermolecular coupling reaction of substrates to give 204 , carbometalation of the latter, β‐elimination of intermediate 205 with cleavage of the C−C bond, and finally intramolecular nucleophilic attack of intermediate 206 to access the target product [129] …”
Section: ‐Alkynylanilines In the Synthesis Of Seven‐ And Eight‐member...mentioning
confidence: 99%
“…[128] Pd(II)-catalyzed treatment of compound bond, and finally intramolecular nucleophilic attack of intermediate 206 to access the target product. [129] Previously we showed that dimerization of 2-alkynylanilines gives substituted quinolines. When dimerization of β-(2-aminophenyl)-α,β-ynones 57 is catalyzed by (JonPhosAuNCMe)SbF 6 , a series of dibenzo [1,5]diazocine 208 is formed through 8-exo-dig intramolecular hydroamination process (Scheme 64).…”
Section: -Alkynylanilines In the Synthesis Of Sevenand Eight-membered...mentioning
confidence: 99%
“…Synthesis of benzo[ b ]naphtho[2,3‐ d ]azocin‐6(5 H )‐ones starting from ( E )‐2‐(2‐bromobenzylidene)cyclobutan‐1‐ones and 2‐alkynylanilines …”
Section: Pd(0)‐catalyzed Processesmentioning
confidence: 99%
“…Intramolecular double bond insertion, followed by aromative rearrangement with ring opening and heterocyclization (by intramolecular nucleophilic displacement), allowed an easy synthesis of benzo[ b ]naphtho[2,3‐ d ]azocin‐6(5 H )‐ones starting from ( E )‐2‐(2‐bromobenzylidene)cyclobutan‐1‐ones and 2‐alkynylanilines (Scheme ) …”
Section: Pd(0)‐catalyzed Processesmentioning
confidence: 99%